MCM-41 supported phosphotungstic acid for the hydroxyalkylation of phenol to phenolphthalein - Jha, Ajay; Garade, Ajit C.; Mirajkar, Subhash P.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2012)
A novel application of phosphotungstic acid, H3PW12O40 (PWA) supported on MCM-41 molecular sieve as a solid acid catalyst has been demonstrated for the synthesis of phenolphthalein by hydroxyalkylation of phenol and phthalic anhydride. PWA/MCM-41 (20%) showed the highest activity as compared to that of parent PWA and MCM-41 individually, due to the excellent dispersion of PWA on MCM-41 leading to the redistribution of Bronsted and Lewis acid sites on MCM-41. The effect of PWA loading on phthalic anhydride conversion and phenolphthalein selectivity was also studied. All these prepared catalysts were characterized by XRD, N-2 adsorption-desorption isotherm, pyridine-FTIR, and NH3-TPD. The effect of various reaction parameters, namely, mole ratios, catalyst concentration, temperature, reaction time, and percentage of PWA present in the catalysts on conversion and selectivity of products has been also investigated. The utility of 20% PWA/MCM-41 catalyst was established by its efficient activity for hydroxyalkylation of phenol and p-cresol with formaldehyde to the corresponding dihydroxydiarylmethane products.

Magnetically separable single-site Ti-Fe3O4@MCM-41 catalyst for selective epoxidation of olefins - Jha, Ajay; Patil, Chetana R.; Garade, Ajit C.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2013)
Magnetically separable Ti-Fe3O4@MCM-41 (Ti-MS) catalysts were prepared by postgrafting Ti with varying loading on mesoporous silica containing dispersed magnetite. The hexagonal structure of Ti-MS catalysts with a periodicity in the pores and a highly ordered hexagonal matrix was established by X-ray diffraction and transmission electron microscopy, while diffuse reflectance UV showed the isolated tetrahedral Ti species coordinated with O2-. From the Fourier transform infrared studies, the extent of Ti-O-Si linkage was found to increase with increase in Ti-loading from 1 to 5 wt %beyond which (10%), the intensity of Ti-O-Si band decreased due to the polymerization of the Ti on the silica surface. Silanol groups on the surface of silica interact with the precursor Ti((OPr)-Pr-i)(4) to give site isolated tetrahedral Ti-species responsible for complete selectivity to the epoxide in the epoxidation of cyclooctene. The magnetic property facilitated easy recovery of the catalyst for its successful eight recycles showing its stability under reaction conditions.

Metal cation-exchanged montmorillonite clay as catalysts for hydroxyalkylation reaction - Jha, Ajay; Garade, Ajit C.; Shirai, M.; Rode, C. V. (Applied Clay Science, 2013)
Several solid acid catalysts were prepared by exchanging metal cations such as Zn2+, Fe3+ and Al3+ with montmorillonite clay. Among these, Al-montmorillonite showed the highest acidity determined by the pyridine-IR as well as NH3-TPD methods. A systematic comparison of the performance of these catalysts along with parent montmorillonite was carried out for the hydroxyalkylation of p-cresol with formaldehyde to give 2, 2'-methylenebis (4-methyl phenol) (DAM). It was found that the activity of these catalysts was in accordance with the increase in acidity of parent montmorillonite after the exchange of cations in the order of Zn2+, Fe3+ and Al3+. The selectivity pattern was also influenced by the exchanged cations. Since Al-montmorillonite showed the highest conversion of 51% with 98% selectivity to DAM, the effects of various reaction parameters, namely, mole ratio, catalyst concentration, temperature, reaction time on conversion and selectivity pattern were also studied using the same catalyst This catalyst also showed an excellent stability as evidenced by its eight times reuse. (C) 2012 Published by Elsevier B.V.
Keywords: Cations-exchanged clay; Montmorillonite; NH3-TPD; Pyridine-IR

Mixed Co-Mn oxide-catalysed selective aerobic oxidation of vanillyl alcohol to vanillin in base-free conditions - Jha, Ajay; Patil, Kashinath R.; Rode, Chandrashekhar V. (Chempluschem, 2013)
Manganese-doped cobalt mixed oxide (MnCo-MO) catalyst was prepared by a solvothermal method. The as-prepared catalyst was characterised by X-ray photoelectron spectroscopy, H-2 temperature-programmed reduction, O-2 temperature-programmed oxidation and XRD. This catalyst gave 62% conversion with 83% selectivity to vanillin in 2hours for the liquid-phase air oxidation of vanillyl alcohol without using base. Three different types of metal oxides were observed in the prepared catalyst, which could be identified as Co3O4, Mn3O4 and CoMn2O4. Among these, the tetragonal phase of CoMn2O4 was found to be more active and selective for vanillyl alcohol oxidation than Co3O4 and Mn3O4. High-resolution TEM characterisation revealed the morphology of MnCo-MO nanorods with a particle size of 10nm. Successful recycling of the catalyst was also established in this oxidation reaction.
Keywords: aerobic oxidation; cobalt; heterogeneous catalysis; manganese; spinel phases

Mesoporous NiCu-CeO2 oxide catalysts for high-temperature water-gas shift reaction - Jha, Ajay; Jeong, Dae-Woon; Jang, Won-Jun; Rode, Chandrashekhar V.; Roh, Hyun-Seog (RSC Advances, 2015)
Mesoporous NiCu-CeO2 oxide catalysts were synthesized by using the evaporation-induced self-assembly method applied to the high-temperature, water-gas shift reaction (HT-WGS) between 350 to 550 degrees C. Nickel and copper loadings on mesoporous ceria were tailored to achieve high activity and selectivity by suppressing methane formation in HT-WGS. Among the prepared catalysts, NiCu(1 : 4)-CeO2 exhibited the highest selectivity to CO2 and H-2 with 85% CO conversion at a very high GHSV of 83 665 h(-1). The higher activity of the catalysts was due to the mesoporous architecture, which provides more accessible active sites for the WGS reaction. Powder X-ray diffraction (XRD), small angle X-ray scattering (SAXS), N-2-adsorption/desorption isotherm, high-resolution transmission electron microscopy (HR-TEM), and H-2-temperature-programmed reduction (TPR) techniques were used to understand the role of mesoporosity and bimetallic composition of various NiCu-CeO2 oxides in enhancing catalytic activity for HT-WGS.